Marketplace, Komunikasi Pemasaran, Dan Inovasi Produk Paving Dalam Meningkatkan Kepuasan Customer UD. Rizka Jaya Abadi Mojosari-Mojokerto - Sumarni Sumarni; Dwi Dewianawati; Erry Setiawan (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2022)
The purpose of this research is to find out the marketplace, marketing communication, and paving product innovation in increasing UD customer satisfaction. Rizka Jaya Abadi Mojosari-Mojokerto. The type of data used in this study uses qualitative data analysis involving 20 informants and the method used in this study uses interview analysis methods. The population in this study are all consumers paving products of UD. Rizka Jaya Abadi Mojosari-Mojokerto. The results of this study indicate that the informants agree that UD. Rizka Jaya Abadi is able to establish good relationships with consumers, informants are satisfied with the products offered and sold by UD. Rizka Jaya Abadi. UD. Rizka Jaya Abadi can increase customer satisfaction through the marketplace or by direct purchases with good marketing communications and product innovations that are diverse and not monotonous